Вміст біологічно активних речовин фенольної природи у представників роду Cynoxylon Raf. - Levon, V.F.; Tesliuk, M.G.; Klymenko, S.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The results of our research antioxidant properties and the content of biologically active substances of phenolic nature in vegetative and generative organs of Cynoxylon species (C. japonica, C. florida, C. capitata) during the growing period of the plants’ life are presented. The most their content was register in the bark, roots, inflorescences, less – in the fruits and shoots.